2002
DOI: 10.1046/j.1365-2958.2002.02741.x
|View full text |Cite
|
Sign up to set email alerts
|

A two‐component signal transduction system involved in nickel sensing in the cyanobacterium Synechocystis sp. PCC 6803

Abstract: Summary In the cyanobacterium Synechocystis sp. PCC 6803, genes for Ni2+, Co2+, and Zn2+ resistance are grouped in a 12 kb gene cluster. The nrsBACD operon is composed of four genes, which encode proteins involved in Ni2+ resistance. Upstream from nrsBACD, and in opposite orientation, a transcription unit formed by the two genes rppA and rppB has been reported previously to encode a two‐component signal transduction system involved in redox sensing. In this report, we demonstrate that rppA and rppB (here redes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 42 publications
0
95
0
Order By: Relevance
“…These genes included sll0797 and sll0798 that encode a two-component system with multiple regulatory roles responding to Ni 2+ , cellular redox and inorganic carbon availability (Li & Sherman, 2000;Ló pez-Maury et al, 2002;Wang et al, 2004a). The gene slr1285 that encodes Hik34 was also downregulated in the wild-type.…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low mentioning
confidence: 99%
“…These genes included sll0797 and sll0798 that encode a two-component system with multiple regulatory roles responding to Ni 2+ , cellular redox and inorganic carbon availability (Li & Sherman, 2000;Ló pez-Maury et al, 2002;Wang et al, 2004a). The gene slr1285 that encodes Hik34 was also downregulated in the wild-type.…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low mentioning
confidence: 99%
“…The chromosome of Synechocystis includes 44 putative genes for Hiks that are candidates for sensors of environmental signals Mizuno et al, 1996). It has already been demonstrated that the Hiks in Synechocystis are involved in the perception and transduction of signals due to cold stress (Suzuki et al, 2000, phosphate deprivation (Hirani et al, 2001;Suzuki et al, 2004), high osmolarity Paithoonrangsarid et al, 2004), heavy metal ions (Ló pez-Maury et al, 2002;Ogawa et al, 2002;Yamaguchi et al, 2002), and high concentrations of NaCl (Marin et al, 2003). In this article, we provide evidence that Hik34, one of the 44 putative Hiks in Synechocystis, is involved in the control of the expression of heat shock genes and the regulation of thermotolerance in Synechocystis.…”
mentioning
confidence: 99%
“…To investigate the dependence of the specific amino acid sequence of the SphS hydrophobic domain on kinase activation and sensing we decided to completely replace this region with the amino acid sequence from the Ni 2+ -sensing histidine kinase NrsS (Lopez-Maury et al, 2002). These two hydrophobic regions have very little amino acid sequence similarity (see Supplementary Fig.…”
Section: Effects Of the Domain Deletions Of Sphs On The Expression Ofmentioning
confidence: 99%